Pemanfaatan Ampas Tahu Dan Daun Kelor Sebagai Media Tambahan Untuk Pertumbuhan Dan Produktivitas Jamur Tiram Putih (Pleurotus ostreatus) - Rahmawati, Jevi Milda; , Dra. Suparti, M.Si (2017)
ofu dregs contains crude fiber content (cellulose, hemicellulose, and lignin) which can be used as an additional medium of white oyster mushrooms. Moringa leaves are rich in nutrients such as proteins, carbohydrates, fiber, and amino acids are benefecial to the growth and productivity of white oyster mushrooms. The purpose of this research is to know the effect of addition of tofu dregs and moringa leaf in planting medium to growth and productivity white oyster mushroom. And to know the weight of tofu dregs and moringa leaf is the most optimal in increasing growth and productivity of white oyster mushroom. The type of research used in the form of experiments wint Randomized Design Complete methode of factorial pattern that is implemented in 2 repetitions. Factor 1 tofu dregs: (Th0) 0 g, (Th1) 50 g, (Th2) 150 g, (Th3) 250 g. Factor 2 Moringa leaves: (K0) 0 g, (K1) 50 g, (K2) 150 g, (K3) 250 g. The parameters measured were the spreading rate of mycelium, quantity of fruit body and the wet weight of oyster mushroom. Data is analyze with One Way Anova. The result showed that treatment of K0Th3 (0 g moringa leaves and 250 g tofu dregs) was the best treatment for the miselium spreading (25,5 days), quantity of fruit body (19,5 pieces), and the wet weight of white oyster mushroom (287,5 g). The treatment of K3Th0 (250 g moringa leaves and 0 g tofu dregs) had the lowest effect on the rate of mycelium spreading (31 days), the number of fruit body (12,75 pieces), and wet weight (237,5 g).